Pengaruh Aplikasi Media Pembelajaran Geogebra Terhadap Kemampuan Berpikir Kritis Dalam Pembelajaran Dan Penyelesaian Persoalan Statistik Pada Prodi Teknik Listrik Bandara - Yayuk Suprihartini; Taryana Taryana (Departement of Mathematics Education, 2023)
Based on the results of the author's initial survey observations, the average training score of students of the Airport Electrical Engineering Study Program.in the work on odd semester statistical questions looks still unsatisfactory, this is due to learning that has not used varied media, lack of good learning planning by choosing learning media that suits student learning styles and so on. So efforts need to be made to improve students' critical thinking skills. This requires the ability to manage teaching and learning activities with the use of appropriate and relevant learning media or applications. Based on the above problems, researchers are interested in conducting research on the application of geogebra learning media to critical thinking skills in learning and solving statistical problems in the Airport Electrical Engineering Study Program. The hypothesis in this study is that there is a significant influence of the application of geogebra learning media on critical thinking skills in learning and solving statistical problems in the Airport Electrical Engineering Study Program. This type of research is quasi-experimental research by providing learning treatment assisted by geogebra learning media in statistical learning. The population in this study was all students who attended statistics lectures, which was 25 people. The instrument used in this study is an essay-shaped problem. The hypothesis test used in this study is the t-test, However, previously normality tests and variance homogeneity tests were carried out. Based on the results of the hypothesis test, a sig value is obtained. (2-tailed) = 0.009 < ∝ = 0.05 so it can be concluded that there is a significant influence of the application of geogebra learning media on critical thinking skills in learning and solving statistical problems in the Airport Electrical Engineering Study Program.